Uji Efek Ekstrak Bawang Dayak (Eleutherine Americana Merr) Terhadap Motilitas Progresif 3 Spermatozoa - NETI EKA JAYANTI; SITI RAUDAH; SUMIATI (Universitas Hang Tuah, 2021)
Abstract Background: Antioxidants in reducing the toxicity of heavy metal lead, one of which is by using dayak onion extract (Eleutherine Americana Merr).The aim of this study was to demonstrate the potential of dayak onion (Eleutherine Americana Merr) extract in maintaining the motility of the testicular spermatozoa of mice induced by lead acetate. Method: The research method used is a laboratory experimental research design using the Posttest Only Control Group Design. The experimental animals used were 30 mice (Mus musculus) divided into 5 groups. The K0 group was a negative control group with 0.1 ml of 0.5% Na-CMC for 38 days. Day 1-3, the K1 positive control group was given 0.5% Na-CMC, the K2-K4 group was given Dayak onion extract at a dose of K2 (30mg / kgBB) K3 (60 mg / kgBB) K4 (120 mg / kgBB). Day 4-38, group K1 was given lead acetate as much as 0.1 ml, K2-K4 was given lead acetate 0.1 ml + dayak extract K2 (30mg / kgBB) K3 (60 mg / kgBB) K4 (120 mg / kgBB) as much as 0.2 ml. Result: There was a significant differences in spermatozoa motility between K0 group with K3, K1 with K3 and K4, K2 with K3. The result of progressive 3 spermatozoa motility between K0 with K1, K2, K3, K4, K1 with K2, K3, K4 showed significant differences, while levels of Conclusion: Dayak onion extract inhibit the decrease in spermatozoa motility of mice , inhibit the decrease in spermatozoa motility, and decrease testicular MDA level in mice induced induced by lead acetate